EFFICIENCY OF COMPLEX USEOF PLANT GROWTH REGULATORS AND MICRO FERTILIZERS IN CULTIVATION OF SPRING BARLEY UNDERWESTERN FOREST-STEPPE CONDITIONS - Tkachuk, S.; Trusheva, Svitlana; Olіinуk Oksana (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The results of the 2016-2017 years research on the variety research station’s lands ofRivne State Regional Center of Plant Variety Expertise (v. Verhivsk Rivnenskyi district)are adduced in the article. Experience scheme included 6 variants with different combinations of plant growth regulators and micro fertilizers for seed treatment or foliar feeding of spring barley’s crops. The results of our research have shown that complex application forseed treatmentof the plant growth regulator Vympel-K (500 g/t) and micro fertilizer Oracle seeds (1 l/t)promote to its germination, extension the growing season, increase of the productive tillering coefficient and disease resistance. One-time barley’s plant foliar feeding with preparations Vympel-K (500 g/ha) and Oracle multikompleks (1 l/ha)alone or in complex provides a significant increase of the spring barley’ syield compared with the control (0,6-0,8 t/ha).The highest grain yield at 4,1 t/ha provides the variant№ 5 – the seed treatment with Vympel-K and Oracle seeds and two-times spraying of spring barley’s crops by plant growth regulator Vympel (500 g/ha).